2022
DOI: 10.1099/mgen.0.000864
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of the genus Delftia reveals distinct major lineages with ecological specializations

Abstract: Delftia is a diverse betaproteobacterial genus with many strains having agricultural and industrial relevance, including plant-growth promotion, bioremediation of hydrocarbon-contaminated soils, and heavy metal immobilization. Delftia spp. are broadly distributed in the environment, and have been isolated from plant hosts as well as healthy and diseased animal hosts, yet the genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 54 publications
4
14
0
Order By: Relevance
“…Delftia spp. are broadly distributed in the environment and have agricultural relevance (Bhat et al 2022 ), the thriving growth of Delftia spp. on different amino acids provides strong evidence of their involvement in the transformation of amino acids within tobacco leaves (Juarez-Jimenez et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Delftia spp. are broadly distributed in the environment and have agricultural relevance (Bhat et al 2022 ), the thriving growth of Delftia spp. on different amino acids provides strong evidence of their involvement in the transformation of amino acids within tobacco leaves (Juarez-Jimenez et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The same was true for the characteristic bacterium Delftia in GZ, which had a significant positive correlation with pinoresinol diglucoside. Previous studies have shown that Delftia has a good application prospect in promoting plant growth and bioremediation (Bhat et al, 2022 ). Some of its members can be used to reduce the accumulation of Cd elements, agricultural inoculants, or bioremediation agents (Bhat et al, 2022 ; Lo et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Delftia has a good application prospect in promoting plant growth and bioremediation (Bhat et al, 2022 ). Some of its members can be used to reduce the accumulation of Cd elements, agricultural inoculants, or bioremediation agents (Bhat et al, 2022 ; Lo et al, 2022 ). In addition, there are other dominant endophytic bacteria including Thauera, Massilia , and Sphingomonas that have significant correlations with EC active ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Several are environmental bacteria that can also act as opportunistic pathogens (Micrococcus, Stutzerimonas, Exiguobacterium, Corynebacterium, Ralstonia, Achromobacter, Acinetobacter), while a few others have industrial relevance, including in enzyme production (Delftia, Exiguobacterium) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these genera are at the same time typical representatives of the normal human microbiome, mostly associated with the skin/mucosa or gut, or pathogens (such as Cutibacterium , Escherichia , Staphylococcus , Pseudomonas , Malassezia , Streptococcus ). Several are environmental bacteria that can also act as opportunistic pathogens ( Micrococcus , Stutzerimonas , Exiguobacterium , Corynebacterium , Ralstonia , Achromobacter , Acinetobacter ), while a few others have industrial relevance, including in enzyme production ( Delftia , Exiguobacterium ) [46].…”
Section: Discussionmentioning
confidence: 99%